PENGARUH JANUARY EFFECT TERHADAP ABNORMAL RETURN SAHAM INDEKS LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2019 - Tirza Oktovianti Lenggono (Jurnal Cita Ekonomika, 2020)
This study aims to examine the effect of the January Effect on Abnormal Return on the LQ-45 Index on the Indonesia Stock Exchange in 2018-2019. The January Effect is an anomalous condition when in January stock prices generally experienced a significant increase. The January Effect was first observed around 1942 by a banker named Sidney B. Wachtel. He noted that since 1925, there has been an increase in share prices in January, especially for small cap stocks. Abnormal return is the difference between actual return and expected return. Abnormal return or abnormal return is the acquisition of profits from the shares obtained. This research is a quantitative research. The population of this study is the LQ-45 Index which is listed on the Indonesia Stock Exchange in 2018-2019. The sampling technique used was purposive sampling and research data were obtained as many as 34 companies from a total of 45 companies. The data analysis method used is simple linear regression. The results of this study indicate that the January Effect has a negative effect on Abnormal Return. Investors are expected to be even more careful in investing by clearly analyzing the issues related to the January Effect.